Tilapia (Oreochromis niloticus) Quality from Pasar Besar Malang - Bayu Kusuma; Angga Wira Perdana; Retno Tri Astuti; Eko Waluyo; Hefti Salis Yufidasari (Journal of Aquaculture Development and Environment, 2019)
Transportation of live tilapia impact evaluated from Pasar Besar, Malang city. Pasar Besar tilapias were supplied from Sidoarjo and Malang Regency. Transportation impact can be identified from tilapia meat quality. pH levels, TVC (Total Viable Count) and TVB (Total Base Nitrogen) determined as tilapia meat quality. pH levels, TVC and TVB showed stress comes from transportation impacted tilapias meat quality.